Performance Improving Techniques for WDM Optical Packet Switching Architecture - Srikoon, J.; Neittanit, Sittipol (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
At present, WDM optical packet switching has been introduced into the all-optical network for enhancement the efficiency of various modern services in the near future. Many technical articles suggested the capability improvement of the switching architecture. And most of these suggestions pinpointed to solve the packet contention problem or the instantaneous conveying of data packet to the same output, which caused the losing of packets and effect to the modern efficiency. Optical buffer, which is cluster of fiber delay lines, is used to collect the discarded packet during contention occurrence in WDM optical packet switching architecture. There are 2 types of optical buffer, which are Output buffer, which located at the output end of the switch, assigned to temporarily collect losing packet during contention occurrences and send out to the output in the next time slot. Shared buffer, which is common with other output buffers and feedback to the input of the switch, assigned to temporarily collect the losing packet and the occupied output buffer during contention. These packets will be sent back to the input of the switch for switching out to the proper output of the next time slot. The consequential effect of this technique is the delaying of the temporary collected packet in the buffer, especially the re-circulating packet between shared buffer and switch or the “Worst Delay Packet”, and finally affect upon the switching capability. This content will by then propose the way to solve packet contention on course of WDM optical packet switching architecture. It will also introduce technique on minimization the delay of “Worst Delay Packet” by queuing prioritization. By the sake of simply internal structure of bypassing queues with fiber delay lines as main function, this will effectively minimize the delay in “Worst Delay Packet” with less side effect to overall system performance. Keywords: optical communication, WDM Corresponding author: E-mail: cast@kmitl.ac.th